Information technology in organisations and societies : multidisciplinary perspectives from AI to technostress - Lee, Zach W. Y.; Chan, Tommy K. H.; Cheung, Christy M. K. (Emerald Publishing Limited, 2021)
Information technology (IT) use has generally been regarded as a positive phenomenon which always generates desirable outcomes. Recent years, however, have witnessed increasing negative consequences resulted from IT use. Emerging issues include individual users have experienced technostress from personal social media usage as well as IT use in the workplace; and organisations have experienced a loss in productivity and assets due to employees' non-compliance with information security policies.Themes explored throughout the book include: AI and its Implications for Organisations Augmented Reality Social Media Stress Cognitive Absorption of Technology Information Technology in Organisations and Societies: Multidisciplinary Perspectives from AI to Technostress represents a collective effort that not only consolidates studies on key issues and phenomena concerning the positive and negative aspects of IT use but also prescribes future research avenues in related research domains. It is particularly relevant to academics and researchers working on IT use research and can be used as a handy reference guide by those working in the field.